2015
DOI: 10.1016/j.bbamcr.2014.09.020
|View full text |Cite
|
Sign up to set email alerts
|

Transglutaminase 2 interacts with syndecan-4 and CD44 at the surface of human macrophages to promote removal of apoptotic cells

Abstract: Tissue transglutaminase (TG2) is a multifunctional protein cross-linking enzyme that has been implicated in apoptotic cell clearance but is also important in many other cell functions including cell adhesion, migration and monocyte to macrophage differentiation. Cell surface-associated TG2 regulates cell adhesion and migration, via its association with receptors such as syndecan-4 and β1 and β3 integrins. Whilst defective apoptotic cell clearance has been described in TG2-deficient mice, the precise role of TG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 53 publications
0
25
0
Order By: Relevance
“…22, 23 Our previous studies have demonstrated that the human monocyte cell line THP-1, when differentiated, provides an effective model for studying the role of macrophages (MØ) in AC clearance and to assess the role of cytokines and other inflammatory mediators released during this process. 5, 24, 25 To understand the impact of gingipains on the expression of important phagocyte receptors, we examined a panel of innate immune receptors on phagocytes before and after treatment with gingipains.…”
Section: Resultsmentioning
confidence: 99%
“…22, 23 Our previous studies have demonstrated that the human monocyte cell line THP-1, when differentiated, provides an effective model for studying the role of macrophages (MØ) in AC clearance and to assess the role of cytokines and other inflammatory mediators released during this process. 5, 24, 25 To understand the impact of gingipains on the expression of important phagocyte receptors, we examined a panel of innate immune receptors on phagocytes before and after treatment with gingipains.…”
Section: Resultsmentioning
confidence: 99%
“…HS chains have also high affinity binding for TG2 Lortat-Jacob et al 2012) which is associated with the HS chains of syndecan-4 in a variety of cell types Lortat-Jacob et al 2012;Nadella et al 2015;Wang et al 2011Teesalu et al 2012). HS proteoglycans have a physiopathological role in the kidney and have also been suggested to modulate TG2 trafficking in the kidney ).…”
Section: Heparan Sulfate Proteoglycans and Tg2 Export In Ckdmentioning
confidence: 96%
“…Recent work indicates the removal of apoptotic cells may also be facilitated by TG2 interaction with syndecan-4 on the surface of human macrophages, whereby the transamidase activity of cell-surface TG2 crosslinks CD44, a phagocytic receptor on human macrophages, to promote apoptotic cell clearance (Nadella et al 2015).…”
Section: Phagocytosismentioning
confidence: 99%